2021
DOI: 10.1159/000518758
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Infection Promotes Human Papillomavirus-Mediated Anal Squamous Carcinogenesis: An Immunologic and Pathobiologic Review

Abstract: <b><i>Background:</i></b> Anal squamous cell carcinoma (SCC) is a rare gastrointestinal malignancy with rising incidence, both in the United States and internationally. The primary risk factor for anal SCC is human papillomavirus (HPV) infection. However, there is a growing burden of disease in patients with human immunodeficiency virus (HIV) and HPV coinfection, with the incidence of anal SCC significantly increasing in this population. This is particularly true in HIV-infected men. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 149 publications
1
34
0
Order By: Relevance
“…According to a recent systematic review, 72% of patients diagnosed with anal cancer were HPV DNA positive [ 5 ]. In addition, several studies have reported a presence of HPV infection in 80% to 97% of patients with diagnosed anal cancer [ 4 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Hpv Infection and Anal Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…According to a recent systematic review, 72% of patients diagnosed with anal cancer were HPV DNA positive [ 5 ]. In addition, several studies have reported a presence of HPV infection in 80% to 97% of patients with diagnosed anal cancer [ 4 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Hpv Infection and Anal Cancermentioning
confidence: 99%
“…There are over 200 known HPV strains. Among them, types 6, 11, 16, and 18 are associated with anal infection [ 4 , 14 ]. Besides these types, some researchers discovered a connection between types 31, 33, and 45 and anal cancer [ 17 ].…”
Section: Hpv Infection and Anal Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…24,25,26 On the other hand, there has been increasing evidence that PD ligand 1 (PD-L1) expression was induced on a variety of cell types by chronic HIV infection. 27,28,29,30 Previous studies have demonstrated that the blockade of PD-1 by using monoclonal antibodies enhanced T cell cycling and differentiation and resulted in rapid expansion of virus-specific CD8 T cells with improved functional quality in simian immunodeficiency virus (SIV)-infected rhesus macaques. 31,32 Those improved immune responses by PD-1 blockade induced significant reductions in plasma viral load and prolonged the survival of SIV-infected macaques.…”
Section: Introductionmentioning
confidence: 99%